PENENTUAN PORTOFOLIO OPTIMAL SAHAM YANG TERGOLONG INDEKS LQ45 MENGGUNAKAN FUNGSI UTILITAS BENTUK PANGKAT - SARI, KADEK INTAN; DHARMAWAN, KOMANG; HARINI, LUH PUTU IDA (E-Jurnal Matematika, 2020)
The proportion of a portfolio can not eliminate risk as a whole but can reduce risk compared to investing in one type of security. One way to determine the optimal portfolio is to use the rank utility function. The purpose of this study is to determine the optimal portfolio of shares of PT. Adhi Karya (Persero) Tbk. (ADHI) and PT. XL Axiata Tbk. (EXCL) for the period January 2017-December 2018 by determining expected returns, variances, standard deviations, covariates, correlation coefficients between shares, and formulating the portfolio equation into a utility function with a rank of 0.5. This study produces a utility value (U (?)) of 0.996181 which means that the level of satisfaction with the proportion of shares of the portfolio is 99.618183%. This value is very high so the proportion of each share is well performed.